A new species of Wimmeria (Celastraceae) from Central America - Jiménez, José Esteban; Barrie, Fred R. (Phytotaxa, 2018)
Wimmeria excoriata, a heretofore undescribed species from the dry forests of Central America, is described and illustrated. It may be distinguished from W. cyclocarpa by its obovate to oblanceolate leaves with rounded apices and larger flowers. It was treated as W. pubescens in the Flora of Nicaragua, but differs from that species in having larger leaves with penninerved secondary venation and larger flowers.